The Armenian Virtual Observatory (ArVO) - Mickaelian, A. M.; Astsatryan, H. V.; Knyazyan, A. V.; Mikayelyan, G. A.; Gevorgyan, Gh.; Baghdasaryan, D. S.; Abrahamyan, H. V.
The Astrophysical Virtual Observatories (AVOs) have been created in a number of countries using their available databases and current observing material as a collection of interoperating data archives and software tools to form a research environment in which complex research programs can be conducted. Among all these data, a large spectroscopic database for all objects is especially useful. The Armenian Virtual Observatory (ArVO) has being created to utilize the Digitized First Byurakan Survey (DFBS) as an appropriate spectroscopic database. ArVO is a project of the Byurakan Astrophysical Observatory (BAO) aimed at construction of a modern system for data archiving, extraction, acquisition, reduction, use and publication. ArVO is based on DFBS and is the Armenian contribution to the International Virtual Observatories Alliance (IVOA). One of the ArVO's main tasks is to create and utilize a global Spectroscopic Virtual Observatory, which will combine data from DFBS and other low-dispersion spectroscopic databases, as well as provide the first understanding on the nature of any object up to B=18 m . In frame of ArVO, BAO collaborates with the Institute of Informatics and Automation Problems (IIAP) of the Armenian National Academy of Sciences to develop software for ArVO corresponding to the IVOA standards. Beside the DFBS, ArVO is being complemented by the Digitized Second Byurakan Survey (SBS) database, the Byurakan photographic archive, and BAO 2.6m and 1m Schmidt telescope observations, and will be a part of IVOA.
Keywords: Astronomy